2018
DOI: 10.1111/pai.12885
|View full text |Cite
|
Sign up to set email alerts
|

YouTube and food allergy: An appraisal of the educational quality of information

Abstract: YouTube videos on food allergy frequently recommend controversial diagnostics and commonly depict non-IgE-mediated reactions. There is a need for high-quality, evidence-based, educational videos on food allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…A poor vid- eos uploaded by non health professions. This is a rate that is comparable to similar studies of information found on YouTube for other diseases, such as food allergies [17], inflammatory bowel disease (24%) [18], anorexia (29%) [19], and rheumatoid arthritis (30%) [20] Lena, et al analyzed the videos on You-Tube about lingual orthodontic treatment that 30.7% (n = 32) of the videos were included high content about treatment and that most videos were uploaded by a layperson (58.7%, n = 61) [21]. Sahin, et al…”
Section: Methodssupporting
confidence: 83%
“…A poor vid- eos uploaded by non health professions. This is a rate that is comparable to similar studies of information found on YouTube for other diseases, such as food allergies [17], inflammatory bowel disease (24%) [18], anorexia (29%) [19], and rheumatoid arthritis (30%) [20] Lena, et al analyzed the videos on You-Tube about lingual orthodontic treatment that 30.7% (n = 32) of the videos were included high content about treatment and that most videos were uploaded by a layperson (58.7%, n = 61) [21]. Sahin, et al…”
Section: Methodssupporting
confidence: 83%
“…Discrepancies in the quality of information of YouTube videos were found not only in the field of dentistry but also in general medicine, such as in orthopedics, or allergy/immunology, where information was deemed to be inadequate and misleading, unlike in endocrinology, where two‐thirds of the videos on type II diabetes were considered useful and half of them had global quality scores which were rated as good or excellent.…”
Section: Discussionmentioning
confidence: 99%
“…A seasonal influenza data quality score was created utilizing a previously published method. [5][6][7][8][9] It was based on the Centers for Disease Control and Prevention (CDC) online information packet "Key Facts about Influenza (flu)." 10 The goal of this scoring system is to evaluate the quality of YouTube web content about seasonal influenza.…”
Section: Methodsmentioning
confidence: 99%